Salvage high-dose chemotherapy in female patients with relapsed/refractory germ-cell tumors: a retrospective analysis of the European Group for Blood and Marrow Transplantation (EBMT) - Giorgi, Ugo de; Dreger, Peter (Annals of oncology, 2017)
AbstractBackground. High-dose chemotherapy (HDC) with hematopoietic progenitor cell transplantation is a standard option for relapsed/refractory testicular ger
Gesehen am 29.08.2018